Genetically modified animals: Options and issues for traceability and enforcement. Issue 2 (August 2015) - Lievens, A.; Petrillo, M.; Querci, M.; Patak, A.
<x xml:space="preserve">Abstract</x> The past two decades have witnessed the rise of commercial crops that have been genetically modified for an increased suitability in extensive cultivation. Currently, a substantial body of research is being carried out in order to produce Genetically Modified (GM) animals that may similarly yield improvements in animal breeding, genetics and reproduction. Here, we attempt a comprehensive review of the existing trails at animal modification with commercial applications and aimed at a deliberate release onto the market. In addition, we investigate detection and quantification options within the frame of food/feed control and traceability on the European market.